1987
DOI: 10.1084/jem.166.6.1654
|View full text |Cite
|
Sign up to set email alerts
|

Localization of antigen on lymph node dendritic cells after exposure to the contact sensitizer fluorescein isothiocyanate. Functional and morphological studies.

Abstract: We have examined the cells involved in the development of contact sensitivity to FITC in CBA mice. After skin painting with antigen, the number of dendritic cells (DC) in the draining lymph nodes increased by 30 min, was maximal at 48 h, and returned to normal by 6 d. Derivation of some DC from Langerhans' cells of the skin was indicated from the presence of Birbeck granules observed in some DC isolated 24 h after skin painting. The DC acquired FITC and by 8 h there were two populations, one highly fluorescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
293
0
2

Year Published

1995
1995
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 531 publications
(308 citation statements)
references
References 37 publications
13
293
0
2
Order By: Relevance
“…injection, the response is likely distributed over several lymph nodes. 31 The mechanical irritation by needle injection may induce local cytokine secretion and activate and recruit additional APC.…”
Section: -Induced Immune Responses To Different Lacz Plasmid Expressimentioning
confidence: 99%
“…injection, the response is likely distributed over several lymph nodes. 31 The mechanical irritation by needle injection may induce local cytokine secretion and activate and recruit additional APC.…”
Section: -Induced Immune Responses To Different Lacz Plasmid Expressimentioning
confidence: 99%
“…When LC encounter exogenous antigens, including haptens and microorganisms, they capture and process them to generate MHC/peptide complexes on their surface. LC migrate from the epidermis to draining lymphoid tissues in order to initiate naive T cells and to present the MHC/peptide complexes to T cells with the necessary adhesion molecules and costimulatory signals [1][2][3][4][5][6][7]. During this migration, LC mature from a dormant into an activated functional state and down-regulate their endocytotic activity.…”
Section: Introductionmentioning
confidence: 99%
“…In CHR, LC first take up antigens by phagocytosis or pynocytosis [7], then they migrate from the epidermis into the regional lymph nodes [22,29]. Our investigation demonstrated that CCB inhibited the capacity of LC to take up and transport antigens to the regional lymph nodes.…”
Section: Discussionmentioning
confidence: 76%
“…After painting of FITC on the skin as hapten, FITC-labelled dendritic cells appeared in the draining lymph nodes [22]. Therefore, we analysed by flow cytometry whether or not CCB affect the ability of LC to take up and transport FITC from the footpads to the popliteal lymph nodes.…”
Section: Reduction Of Dncb-induced Ear Swellingmentioning
confidence: 99%